Patient-Reported Experience Measures in outpatient rheumatology care: a systematic review. Issue 3 (30th October 2021) - Bryant, Madeleine J; Schubert, Jonathon P; Black, Rachel J; Hill, Catherine L
Abstract: Objectives: There is a growing acceptance of the need for routine implementation of patient-reported experience measures (PREMs) in health care. Rheumatology patients, as frequent and long-term users of care, stand to benefit from collection of experience-related data. The aim of this study was to perform a systematic review to identify and critically appraise the development and psychometric validation of PREMs in rheumatology. Methods: Six databases were searched systematically from inception to 14 December 2020: MEDLINE, EMBASE, PsycINFO, SCOPUS, Cochrane and Google Scholar. We included articles in English that described the use or development of PREMs, with results of psychometric testing, in an adult outpatient rheumatology context. This study is registered with PROSPERO (CRD42021233819). Articles were appraised using the COnsensus Based Standards for the selection of health status Measurement Instruments (COSMIN) (i) Risk of Bias checklist and (ii) criteria for good measurement properties. Results: The search yielded 3809 publications, and six studies met inclusion criteria. All the included studies on PREM development fulfilled COSMIN standards for 'doubtful' or 'inadequate' quality of instrument development. One study fulfilled a 'sufficient' rating for content validity, and the remainder fulfilled 'inconsistent' ratings. During validity testing, studies fulfilled between one and four of the eight COSMIN checklist criteria for good measurement properties. Conclusion: Methodological concerns regarding instrument development and validation limit the generalizability of the existing six validated PREMs in use in rheumatology contexts. There is a need for further well-designed studies to validate existing and new PREMs in this area.